Health sector decentralization and divergences with the medical society in Mexico - Abrantes Pêgo, Raquel; Arjonilla Alday, Sofía (Revista de Saúde Pública, 2002)
OBJECTIVE: To evaluate the medical society's perception and actions in the context of health sector decentralization in the states of Guanajuato and Sonora, Mexico. METHODS: Qualitative research techniques were applied. Thirty-five semi-structured interviews were conducted with medical college members of both public and private institutions, and collegiate and union representatives of both states studied. RESULTS: Members of medical society in both states acknowledged that decentralization implied in insecurity due to the lack of clarity of health sector regulations. As a result of actions of the medical college in both states there was a growing politicization of medical college members, elaboration of proposals to increase their control over the medical labor market and their participation in the regional political power structure. CONCLUSIONS: This research supports the existing re-articulation of the medical society at a regional level preserving its status as a respected group. In contrast to studies conducted in the United States and Mexico medical authorities have pressed on the regulations in order to preserve their privileged status within the existing contention.